2021
DOI: 10.1074/jbc.ra120.015293
|View full text |Cite
|
Sign up to set email alerts
|

Linker residues regulate the activity and stability of hexokinase 2, a promising anticancer target

Abstract: Hexokinase (HK) catalyzes the first step in glucose metabolism, making it an exciting target for the inhibition of tumor initiation and progression due to their elevated glucose metabolism. The upregulation of hexokinase-2 (HK2) in many cancers and its limited expression in normal tissues makes it a particularly attractive target for the selective inhibition of cancer growth and the eradication of tumors with limited side effects. The design of such safe and effective anticancer therapeutics requires the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The two HK2 catalyzing domains convert glucose to Glucose-6-phosphate (G-6-P) that is a rate-limiting manner in glycolysis 29 , 30 . Point mutations at both N-terminal and C-terminal catalytic domains (D209A and D657A) of HK2 effectively diminish the enzymatic activity of HK2 29 , 31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two HK2 catalyzing domains convert glucose to Glucose-6-phosphate (G-6-P) that is a rate-limiting manner in glycolysis 29 , 30 . Point mutations at both N-terminal and C-terminal catalytic domains (D209A and D657A) of HK2 effectively diminish the enzymatic activity of HK2 29 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…The two HK2 catalyzing domains convert glucose to Glucose-6-phosphate (G-6-P) that is a rate-limiting manner in glycolysis 29 , 30 . Point mutations at both N-terminal and C-terminal catalytic domains (D209A and D657A) of HK2 effectively diminish the enzymatic activity of HK2 29 , 31 . To explore the metabolic consequences of HK2 upregulation in senescence, we conducted 13 C glucose isotope tracing in control and senescent cells with or without HK2 knockdown, and then rescued with ectopic expression of either wildtype or enzymatic activity inactive mutant HK2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High-throughput screening expedites the identification of potential structures, resulting in significant time and cost savings. Precise drug development is enhanced by targeting specific residues [ 183 ], while drug repositioning and formulation modification are effective strategies to discover new drugs and minimize expenses and time consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they proposed that these residues serve as a regulatory site for HK II, which could be targeted to specifically inhibit the enzyme. This inhibition, in turn, could effectively reduce the rate of cancer glycolysis, offering a promising avenue for the development of novel anticancer drugs [ 183 ]. Additionally, in a study conducted by Ruiqi Li et al, mutations such as V431Cfs*26, L795Rfs*10, and A901Rfs*74 were found in cases of gastric adenocarcinoma (STAD), lung squamous carcinoma (LUSC), and endometrial carcinoma (UCEC).…”
Section: Hk II Inhibitorsmentioning
confidence: 99%
“…The qPCR instrument was equipped with a Peltier‐based thermal system for uniform temperature ramping and thermal accuracy to ensure reproducibility of the data. The data were fitted to Boltzmann sigmoidal function using the Excel add‐on package XLfit (IDBS limited, Bridgewater, NJ), and the T m was calculated at the middle of the denaturation transition as described previously 42 . The T m value of 3CLpro was measured at different DMSO concentrations to determine its effect on the stability of the protease in a buffer containing 20 mM Hepes, pH 7.0, 150 mM NaCl, 1 mM EDTA, and 1 mM TCEP.…”
Section: Methodsmentioning
confidence: 99%